Working characteristics of young physicians graduated from San Fernando School of Medicine - Huamán, Moisés (2007)
Objective: To determine the working characteristics of young physicians graduated from San Fernando School of Medicine. Design: Observational, transversal study. Setting: San Fernando School of Medicine, Universidad Nacional Mayor de San Marcos. Participants: Physicians graduated from the School of Medicine. Interventions: Information about sociodemographics, work performance, professional degree, satisfaction level and extracurricular performance during pregrade was collected directly, by phone interview or by e-mail questionnaire from 232 randomly selected physicians graduated between 1994 and 2003. We also obtained pregrade final scores. Main outcome measures: Working rate, labor type, work performance, especialization. Results: From all subjects 72,4% were men, 73,2% lived in Lima, 19,3% lived outside of Lima and 7,5% abroad; 97% had remunerated work, 51,4% had two or more jobs; 71% worked for public institutions. The predominant kind of work was clinical; 78,8% reached the required work performance; 64,9% was specialized; 15,4% had or studied for a master degree. No relationship between pregrade factors and work or professional characteristics was found. Conclusions: Working rate was high. Centralism, multiple jobs, clinical care in public hospitals and tendency to become specialized were predominant.